Control of the workplace environment by physical factors and smart monitoring - Kruzhilko, O. Ye.; Polukarov, O. I.; Vambol, S.; Vambol, V.; Khan, N. A.; Maystrenko, V. V.; Kalinchyk, V. P.; Khan, A. H.; Кружилко, О. Є.; Майстренко, В. В. (Association for Computational Materials Science and Surface Engineering, 2020)
To develop and implementation in practice an algorithm for smart monitoring of workplace environmental physical factors for occupational health and safety (OSH) management.
Keywords: Environmental physical factors; Occupational health; Monitoring; Occupational safety and health management system; Decision-making algorithm